Teamwork Pengembangan Kemitraan (Studi Kasus Kelompok Kerja Pengembangan Kemitraan dalam Penangulangan Kemiskinan di Kota Bogor) - Lestari, Rizki Bunga; Nulhaqim, Soni Akhmad; Irfan, Maulana (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2015)
The title of this research is “Teamwork of Development Partnership (Case Study Development Partnership Teamwork of Poverty in Bogor)”. This research aims to describe the teamwork process conducted by the Working Group on Development Partnership include communication, compromise, cooperation, coordination, and consummation. Teamwork that made the Working Group in an effort to reduce poverty in Bogor. Researcher used a qualitative research approach with case study method, while the instruments used in data collection is interview, observation guidelines, and guidance documentation. The technique used an in-depth interviews, non-participatory observation, and literature study. Informants in this research is 11 people, they are 4 persons from SKPD, 2 persons from BUMD, 2 persons from BUMN, and 3 persons from private sector. The results of this research indicate that good teamwork is determined by communication, compromise, cooperation, coordination, and consummation. Communications flow into upward, downward, and horizontal, both formally and informally, through the medium of verbal and non-verbal communication. Compromises is used to resolve the differences that determined the best alternative. Cooperation as a form of cooperation through the participation of members in carrying out its duties and responsibilities. Coordination is used to integrate the goals and activities of the Working Group in order to direct, there is no overlap. Then, the consummation is used through improvements in poverty reduction activities in Bogor. Thus, the researchers suggest a training program “Team Building Training to Improve the Quality of Teamwork”. The purpose of this training is to raise awareness of Pokja members so that they understand the importance of teamwork that goes with effective and implement a strategy or technique in achieving teamwork, so that the Pokja was able to develop and implement effective teamwork in tackling poverty.Keywords: Human Service Organization, Teamwork, Komunikasi dan Kooperasi